Acute hyperammonemia activates branched-chain amino acid catabolism and decreases their extracellular concentrations: different sensitivity of red and white muscle - Holecek, Milan; Kandar, Roman; Sispera, Ludek; Kovarik, Miroslav (Amino acids, 2011)
Hyperammonemia is considered to be the main cause of decreased levels of the branched-chain amino acids (BCAA), valine, leucine, and isoleucine, in liver cirrhosis. In this study we investigated whether the decrease in BCAA is caused by the direct effect of ammonia on BCAA metabolism and the effect of ammonia on BCAA and protein metabolism in different types of skeletal muscle. M. soleus (SOL, slow-twitch, red muscle) and m. extensor digitorum longus (EDL, fast-twitch, white muscle) of white rat were isolated and incubated in a medium with or without 500 μM ammonia. We measured the exchange of amino acids between the muscle and the medium, amino acid concentrations in the muscle, release of branched-chain keto acids (BCKA), leucine oxidation, total and myofibrillar proteolysis, and protein synthesis. Hyperammonemia inhibited the BCAA release (81% in SOL and 60% in EDL vs. controls), increased the release of BCKA (133% in SOL and 161% in EDL vs. controls) and glutamine (138% in SOL and 145% in EDL vs. controls), and increased the leucine oxidation in EDL (174% of controls). Ammonia also induced a significant increase in glutamine concentration in skeletal muscle. The effect of ammonia on intracellular BCAA concentration, protein synthesis and on total and myofibrillar proteolysis was insignificant. The data indicates that hyperammonemia directly affects the BCAA metabolism in skeletal muscle which results in decreased levels of BCAA in the extracellular fluid. The effect is associated with activated synthesis of glutamine, increased BCAA oxidation, decreased release of BCAA, and enhanced release of BCKA. These metabolic changes are not directly associated with marked changes in protein turnover. The effect of ammonia is more pronounced in muscles with high content of white fibres.
Keywords: Liver Cirrhosis; modely nemocí na zvířatech; Male; Rats, Wistar; Ammonia; větvené aminokyseliny; Muscle, Skeletal; Amino Acids, Branched-Chain; mužské pohlaví; potkani Wistar; kosterní svaly; krysa rodu Rattus; akutní nemoc; Acute Disease; Animals; extracelulární prostor; lidé; hyperamonemie; jaterní cirhóza; Extracellular Space; Humans; amoniak; zvířata; Rats; Hyperammonemia; Disease Models, Animal